2014
DOI: 10.1017/jfm.2014.326
|View full text |Cite
|
Sign up to set email alerts
|

Mutual inductance instability of the tip vortices behind a wind turbine

Abstract: Two modal decomposition techniques are employed to analyse the stability of wind turbine wakes. A numerical study on a single wind turbine wake is carried out focusing on the instability onset of the trailing tip vortices shed from the turbine blades. The numerical model is based on large-eddy simulations (LES) of the Navier-Stokes equations using the actuator line (ACL) method to simulate the wake behind the Tjaereborg wind turbine. The wake is perturbed by low-amplitude excitation sources located in the neig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
107
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(123 citation statements)
references
References 26 publications
7
107
0
Order By: Relevance
“…The shear profile is implemented to match the profile given in the invitational document by Saetran and Bartl (2015). A more detailed description of the method can be found in Sarmast et al (2014).…”
Section: Uppsala University and Dtu (Uu-dtu)mentioning
confidence: 99%
See 1 more Smart Citation
“…The shear profile is implemented to match the profile given in the invitational document by Saetran and Bartl (2015). A more detailed description of the method can be found in Sarmast et al (2014).…”
Section: Uppsala University and Dtu (Uu-dtu)mentioning
confidence: 99%
“…The largest rotor investigated for wake comparison studies was the MEXICO rotor, with a diameter of 4.5 m (Schepers et al, 2010), in which the rotor performance as well as the wake flow were examined in detail. A second campaign investigating even more effects, including span-wise pressure distributions, yaw misalignment and unsteady effects, was realized at a large German-Dutch Wind Tunnel (DNW).…”
Section: Introductionmentioning
confidence: 99%
“…The initial derivations of the presented analysis follow the work of Ivanell et al [23] and Sarmast et al [28]. In these studies, the simulations are performed using the Tjaereborg wind turbine operating at the optimum power condition (Cp = 0.49) for a wind speed of U 0 = 10 m s −1 and tip speed ratio of λ = 7.…”
Section: (A) Stability Analysis Of Tip Vorticesmentioning
confidence: 99%
“…From the figure, it can be clearly seen that the amplitudes develop with an exponential growth rate. More information regarding the computations can be obtained from Ivanell et al [23] and Sarmast et al [28]. The curves are normalized by the amplitude at x/R = 0.5 to compare the growth from computations with different perturbations.…”
Section: (A) Stability Analysis Of Tip Vorticesmentioning
confidence: 99%
“…Another dynamic approach, also followed in this work, is to analyse and model wind turbine wakes using modal decompositions [21,[35][36][37][38][39][40][41][42][43][44][45][46][47] which describe the velocity field as a linear superposition of spatial modes with time-dependent weighting coefficients. It has been shown that a few spatial modes can already capture important features of the wake flow [35][36][37][38][39]41,43,47].…”
Section: Introductionmentioning
confidence: 99%